Detection, formation and occurrence of 13 new polar phenolic chlorinated and brominated disinfection byproducts in drinking water. (1st April 2017) - Pan, Yang; Wang, Ying; Li, Aimin; Xu, Bin; Xian, Qiming; Shuang, Chendong; Shi, Peng; Zhou, Qing
Abstract: Recently, 13 new polar phenolic chlorinated and brominated disinfection byproducts (Cl- and Br-DBPs) were identified and quantified in simulated chlorinated drinking water by adopting product ion scan, precursor ion scan, and multiple reaction monitoring (MRM) analyses using ultra performance liquid chromatography/electrospray ionization-triple quadrupole mass spectrometry (UPLC/ESI-tqMS). The 13 new DBPs have been drawing increasing concern not only because they possess significantly higher growth inhibition, developmental toxicity, and chronic cytotoxicity than commonly known aliphatic DBPs, but also because they act as intermediate DBPs that can decompose to form the U.S. EPA regulated DBPs. In this study, through MS parameter optimization of the UPLC/ESI-tqMS MRM analysis, the instrument detection and quantitation limits of the 13 new DBPs were substantially lowered to 0.42–6.44 and 1.35–16.51 μg/L, respectively. The total levels of the 13 new DBPs formed in chlorination were much higher than those formed in chloramination within a contact time of 3 d. In chlorination, the 13 new DBPs formed quickly and decomposed rapidly, and their total concentration kept on decreasing with contact time. In chloramination, the levels of the dominant species (i.e., trihalo-phenols) firstly increased and then decreased with contact time, whereas the levels of the other new DBPs were relatively low and kept on increasing with contact time. An increasing of pH from 6.0 to 9.0 decreased the formation of the 13 new DBPs by 57.8% and 62.3% in chlorination and chloramination, respectively. Gallic acid was found to be present in various simulated and real source water samples and was demonstrated to be a precursor of the 13 new DBPs with elucidated formation pathways. Furthermore, 12 of the 13 new DBPs were detected in 16 tap water samples obtained from major cities in East China, at total levels from 9.5 to 329.8 ng/L. The concentrations of the new DBPs were higher in samples with source waters containing higher bromide levels. Ozone-activated carbon treatment prior to disinfection might reduce the formation of the new DBPs since it was effective in precursor reduction. Graphical abstract: Highlights: UPLC/ESI-tqMS parameters were optimized for better detection of the 13 new DBPs. Disinfectant, contact time, and pH all affected the formation of the 13 new DBPs. Gallic acid was confirmed to be the precursor of the 13 new DBPs. Formation pathways of the 13 new DBPs from gallic acid were elucidated. Occurrence of the 13 new DBPs in 16 Chinese tap water samples was investigated.